When space becomes art - Marisa, Cláudia (2017)
Peter Brook claims that a space shared by the “emitter” and “receptor” is an intrinsic element of artistic interaction. We can therefore argue that actions taking place in public spaces are performed according to shared rules within a known set of expectations. There is always an interchange of roles between the “emitter” (or performer; the promoter of the action) and the “receptor” (or spectator; the witness of the action). This interchange is crucial to the creation of a symbolic system. It follows therefore that all kinds of space are – potentially – scenic spaces. It is worth mentioning that it was not until Richard Wagner insisted on turning off the lights in the auditorium that the stage became a “solo” space. Until then, theatre architecture included the audience in the event of the play.